Case Report: autologous stem cell boost enables hematopoietic recovery after severe cytopenia induced by BCMA-targeted bispecific antibody therapy in multiple myeloma - Akiyama, Hiroaki; Kakiuchi, Seiji; Sakamoto, Akimasa; Tomigaki, Naru; Fujioka, Shutaro; Harima, Isamu; Niwa, Ryotaro; Takagi, Ikumi; Kozuki, Yoko; Miyata, Yoshiharu; Yoshihara, Kyoko; Yoshihara, Satoshi; et al. (Frontiers in Oncology, 2026)
Elranatamab, a bispecific antibody targeting B-cell maturation antigen (BCMA) and CD3, has shown significant efficacy in relapsed or refractory multiple myeloma (RRMM). However, elranatamab therapy also carries a risk of hematologic toxicity. Stem cell boost (SCB), involving reinfusion of previously collected autologous CD34+ hematopoietic stem cells, has been explored as a salvage strategy after Chimeric Antigen Receptor T-cell (CAR T-cell) therapy-related cytopenias. To date, its role following bispecific antibody treatment remains unclear. We report the case of a 59-year-old man with RRMM who developed prolonged pancytopenia after elranatamab therapy, successfully rescued with autologous SCB. Neutrophil recovery occurred by day +10, transfusion independence by day +19, and hematologic recovery allowed elranatamab resumption without recurrence of severe cytopenia. This case demonstrates the potential utility of SCB for managing persistent cytopenias after T-cell–redirecting therapies and supports the importance of early stem cell collection.